ANTIBACTERIAL EFFECTS OF MESENCHYMAL STEM CELL SECRETOME ON THE GROWTH OF PATHOGENIC BACTERIA - Parti Putri; Tri Juanda (Journal of Stem Cell Research and Tissue Engineering, 2026)
Bacterial infection remains a major global health problem due to the increasing emergence of antibiotic-resistant microorganisms. Mesenchymal stem cell (MSC) secretome has attracted attention as a potential cell-free therapeutic approach because it contains bioactive molecules with antimicrobial, immunomodulatory, and regenerative properties. This study aimed to evaluate the antibacterial activity of MSC secretome against pathogenic bacteria in vitro. This experimental laboratory study used a post-test only control group design. Human dental pulp-derived MSCs were cultured under standard conditions, and conditioned medium containing secretome was collected and processed. Antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa was evaluated using agar diffusion and bacterial viability assays. Experimental groups included control, low-, medium-, and high-concentration secretome treatments. Inhibition zone diameters and Log10 CFU/mL values were analyzed using one-way ANOVA followed by Tukey post hoc test with a significance level of p < 0.05. The results showed that MSC secretome significantly inhibited bacterial growth compared with the control group. Antibacterial activity increased proportionally with secretome concentration, as demonstrated by larger inhibition zones and lower bacterial viability values. The highest antibacterial activity was observed in the high-concentration secretome group, which reduced bacterial viability by approximately 70–80%. Staphylococcus aureus showed greater susceptibility than Gram-negative bacteria, particularly Pseudomonas aeruginosa. Statistical analysis confirmed significant differences among treatment groups (p < 0.05). In conclusion, MSC secretome demonstrated significant concentration-dependent antibacterial activity against pathogenic bacteria in vitro. These findings suggest that MSC secretome may serve as a promising cell-free therapeutic strategy for infectious disease management and regenerative medicine.